Pendekatan Realistic Mathematics Education (RME) dalam Meningkatkan Kemampuan Pemecahan Masalah dan Representasi Matematis Siswa Sekolah Dasar: Literatur Review - Nurhikmah; Mawaddah Subhan; Nur Wahyuni Ainul Alwi Muslimin; Hamda; Syahrul Syawal (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The low problem-solving and mathematical representation abilities of elementary school students in mathematics learning are problems that require special attention. This study aims to: (1) describe the Realistic Mathematics Education (RME) approach in improving elementary school students' problem-solving and mathematical representation abilities; (2) identify the benefits of RME on students' mathematical problem-solving abilities through the use of real contexts; and (3) analyze the challenges faced in implementing RME in the classroom. This study uses a literature study method with a content analysis approach to relevant scientific articles and journals published in the last five years. The results show that the implementation of RME can improve students' problem-solving abilities by providing them with opportunities to solve mathematical problems related to real life. In addition, RME is also effective in developing mathematical representations, such as the use of symbols, images, and tables, which help students understand mathematical concepts better. However, challenges applied in implementing RME include time constraints, lack of appropriate open materials, and differences in students' abilities in understanding contexts. This study confirms that RME is a highly relevant and effective approach in creating more meaningful, contextual, and active mathematics learning at the elementary school level.